The Effect of Corrective Exercises Based on the Davis Model on Improving the Learning of Passing and Shooting Skills in Football (Journal of the College of Basic Education, 2026)
The objective of the study was to design educational exercises based on the Davis model to support the learning of handling and scoring skills, and to examine their effect on acquiring handling and rolling skills among fifth-grade middle school students.The researcher employed the experimental method using a one-group design with pre- and post-tests. The research sample consisted of fifth-grade students at Al-Azami Secondary School, selected randomly. The experimental group included 20 students, while 5 students from Division B were selected as an exploratory group for pilot testing, making up 22.727% of the total population.Conclusions:The exercises developed by the researcher in accordance with the Davis strategy had a positive impact on learning handling and scoring skills in indoor football. Implementing the strategy helped establish a structured and clear educational environment. The participants demonstrated significant improvement in skill performance, as evidenced by the differences observed in the post-test results. Additionally, the application of the Davis strategy enhanced students' awareness and identification of their technical errors.Recommendations:The researcher recommends adopting educational exercises that follow the Davis strategy. Furthermore, the use of modern teaching methods and strategies is encouraged to support learners with delayed progress, helping them reach levels comparable to their peers.